Personal investment theory: A multi-faceted framework to understand second and foreign language motivation. (November 2019) - King, Ronnel B.; Yeung, Susanna Siu-Sze; Cai, Yuyang
Abstract: The aim of this article is to introduce second and foreign language researchers to personal investment theory, a classic motivation theory that takes a multi-faceted approach to understand when and why learners invest themselves in a particular domain. Personal investment theory posits that there are three key components of meaning–(1) facilitating conditions, (2) sense of self, and (3) perceived goals–which are crucial to understanding motivation and learning. The paper gives an overview of the key tenets of personal investment theory and illustrates the synergies between this theory and research in second and foreign language learning. Although personal investment theory has seldom been used in second and foreign language research, a case is made for how it can enrich mainstream second and foreign language theorizing. Personal investment theory has key strengths including its integrative multi-faceted approach to understanding motivation, sensitivity to the role of socio-cultural influences, focus on powerful yet neglected constructs, and its recognition of cross-cultural similarities and differences. The paper concludes with recommendations for optimizing second and foreign language learning.